Assessment of corporate social responsibility by addressing sustainable development goals. (15th November 2020) - Lu, Jintao; Liang, Mengshang; Zhang, Chong; Rong, Dan; Guan, Hailing; Mazeikaite, Kristina; Streimikis, Justas
Abstract: The aim of this study is to discuss the issues relevant to the CSR evaluation and to develop a model of CSR assessment by taking into account SDGs. Based on a critical literature review, the advantages and limits of CSR assessment models were analyzed with the SDGs addressed, and the framework of a novel model of CSR assessment was proposed in this study. The main limitations of CSR in addressing SDGs were defined as follows: the selective implementation of SDGs, greenwashing, the lack of the integration of the stakeholders, the lack of incorporation of SMEs, and the difference in CSR practices among countries. The created model includes all SDGs involved. Moreover, the positive and negative effects of CSR on SDGs were addressed. This proposed CSR assessment model can help to solve the major problems described above: selective implementation of SDGs, greenwashing, and the inability to compare CSR among industries or countries.